Twitch force in human Amyotrophic Lateral Sclerosis - Libonati, Laura; Cambieri, Chiara; Ceccanti, Marco; Moret, Federica; Di Giulio, Matteo; Palma, Eleonora; Inghilleri, Maurizio (Frontiers in Neurology, 2025)
IntroductionThis study investigated differences in muscle twitch force between slow and fast progressors of amyotrophic lateral sclerosis (ALS) to better understand disease heterogeneity and identify potential biomarkers of disease progression.MethodsForty-four ALS patients were classified as slow or fast progressors based on disease progression rates. Electrophysiological assessments, including compound muscle action potential (CMAP) and muscle force measurements, were conducted. Creatine kinase (CK) levels were also evaluated.ResultsSlow progressors demonstrated significantly higher muscle peak force and area under the curve (AUC) compared to fast progressors, reflecting greater muscle strength and endurance. CK levels were also elevated in slow progressors.DiscussionDespite similar CMAp values, slow progressors retained greater muscle strength, possibly due to a reduced degeneration of fast-twitch fibers and compensatory axonal sprouting. These adaptations may preserve muscle function and elevate CK levels, suggesting better muscle integrity in slow progressors.ConclusionMuscle function profiles and CK levels are promising indicators of ALS progression. These findings could enhance early detection of disease progression and lead to targeted interventions to preserve muscle function. Further research is needed to validate these results and explore the underlying functional mechanisms of disease heterogeneity.